Incremental Value of Larger Interventricular Conduction Time in Improving Cardiac Resynchronization Therapy Outcome in Patients with Different QRS Duration. (4th March 2014) - D'ONOFRIO, ANTONIO; BOTTO, GIANLUCA; MANTICA, MASSIMO; LA ROSA, CONCETTO; OCCHETTA, ERALDO; VERLATO, ROBERTO; MOLON, GIULIO; AMMENDOLA, ERNESTO; VILLANI, GIOVANNI Q.; BONGIORNI, MARIA GRAZIA; BIANCHI, VALTER; GELMINI, GIAN PAOLO; et al.
Interventricular Electrical Delay Introduction The left ventricular (LV) pacing site and the magnitude of the electrical delay within the LV, as expressed by prolonged QRS duration, are major determinants of cardiac resynchronization therapy (CRT) efficacy. We investigated the incremental value of positioning the LV lead in areas of late activation in order to enhance the response to CRT in patients with different degrees of QRS complex lengthening. Methods and Results This analysis was performed on 301 heart failure patients who received a CRT defibrillator. On implantation, the right ventricular (RV)‐to‐LV interval was measured as the delay between local activations recorded through the RV and LV leads in the final position. After 1 year, 171 (57%) patients displayed reverse LV remodeling, as measured by a ≥15% reduction in the LV end‐systolic volume. Both the RV‐to‐LV interval and its percentage value corrected for the QRS duration were significantly associated with a positive response to CRT. An RV‐to‐LV interval >80 milliseconds and an RV‐to‐LV interval/QRS >58% yielded the best prediction of reverse remodeling. Although the response to CRT decreased with shorter QRS duration in the overall population, patients with an RV‐to‐LV interval >80 milliseconds showed a response rate >65% in all QRS subgroups. Conclusion A longer RV‐to‐LV interval is associated with reverse LV remodeling after CRT. On implantation attempts could be made to maximize it when selecting the LV lead position, especially in patients with shorter QRS duration, and thus less likely to respond positively to CRT.